1997
DOI: 10.1083/jcb.136.1.61
|View full text |Cite
|
Sign up to set email alerts
|

The Autophagic and Endocytic Pathways Converge at the Nascent Autophagic Vacuoles

Abstract: We used an improved cryosectioning technique in combination with immunogold cytochemistry and morphometric analysis to study the convergence of the autophagic and endocytic pathways in isolated rat hepatocytes. The endocytic pathway was traced by continuous uptake of gold tracer for various time periods, up to 45 min, while the cells were incubated in serum-free medium to induce autophagy. Endocytic structures involved in fusion with autophagic vacuoles (AV) were categorized into multivesicular endosomes (MVE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
210
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(220 citation statements)
references
References 22 publications
7
210
0
3
Order By: Relevance
“…The observation that lipid modulation at the plasma membrane has an impact on autophago-lysosomal accumulation argues in favor of two long debated issues in the autophagy field. They support the convergence of autophagy and endocytic pathways 41,42 and the contribution of the plasma membrane to the formation of the autophagosome membrane. 27,43,44 We believe these findings open interesting perspectives for NPA treatments aimed at avoiding SM accumulation at the plasma membrane, which could be a more accessible target than lysosomes.…”
Section: Discussionsupporting
confidence: 52%
“…The observation that lipid modulation at the plasma membrane has an impact on autophago-lysosomal accumulation argues in favor of two long debated issues in the autophagy field. They support the convergence of autophagy and endocytic pathways 41,42 and the contribution of the plasma membrane to the formation of the autophagosome membrane. 27,43,44 We believe these findings open interesting perspectives for NPA treatments aimed at avoiding SM accumulation at the plasma membrane, which could be a more accessible target than lysosomes.…”
Section: Discussionsupporting
confidence: 52%
“…Others believed that the convergence might be a multistage event [14][15][16]. In the present study, the endocytic and autophagic compartments can be readily identified in Leydig cells, which makes easier to define the stages of two pathways than was possible before.…”
Section: The Convergent Point Of Endocytic and Autophagic Pathwaysmentioning
confidence: 69%
“…The appearance of heterologous transforming vacuoles after leupeptin treatment suggests that MLBs are continually fusing with lysosomes and that transformation of newly incorporated material into membrane lamellae requires lysosomal degradation. The endocytic pathway has been shown to deliver material to nascent autophagic vacuoles, and the autophagic pathway is therefore accessible at early stages (Gordon and Seglen, 1988;Tooze et al, 1990;Liou et al, 1997). Fusion of lysosomes with degradative autophagic vacuoles has also been documented (Ericsson, 1969;Lawrence and Brown, 1992;Yokota et al, 1995).…”
Section: Role Of Lysosomal Degradation In Mlb Biogenesismentioning
confidence: 99%